A Cohort Study on the Duration of Plasmodium falciparum Infections During the Dry Season in The Gambia . (5th April 2022) - Collins, Katharine A; Ceesay, Sukai; Drammeh, Sainabou; Jaiteh, Fatou K; Guery, Marc Antoine; Lanke, Kjerstin; Grignard, Lynn; Stone, Will; Conway, David J; D'Alessandro, Umberto; Bousema, Teun; Claessens, Antoine
Abstract: Background: In areas where Plasmodium falciparum malaria is seasonal, a dry season reservoir of blood-stage infection is essential for initiating transmission during the following wet season. Methods: In The Gambia, a cohort of 42 individuals with quantitative polymerase chain reaction-positive P falciparum infections at the end of the transmission season (December) were followed monthly until the end of the dry season (May) to evaluate infection persistence. The influence of human host and parasitological factors was investigated. Results: A large proportion of individuals infected at the end of the wet season had detectable infections until the end of the dry season (40.0%; 16 of 40). At the start of the dry season, the majority of these persistent infections (82%) had parasite densities >10 p/µL compared to only 5.9% of short-lived infections. Persistent infections (59%) were also more likely to be multiclonal than short-lived infections (5.9%) and were associated with individuals having higher levels of P falciparum -specific antibodies ( P  = .02). Conclusions: Asymptomatic persistent infections were multiclonal with higher parasite densities at the beginning of the dry season. Screening and treating asymptomatic infections during the dry season may reduce the human reservoir of malaria responsible for initiating transmission in the wet season. Abstract : In The Gambia, a cohort of individuals asymptomatically infected with P falciparum was sampled monthly over the dry season. Higher density multiclonal infections were more likely to persist during the dry season.